P1 adhesin genotype characteristics of Mycoplasma pneumoniae in China from 2017 to 2019 - Li, Shirong; Dou, Haiwei; Shi, Dawei; Yuan, Ruijie; Tu, Peng; Yuan, Qing; Xin, Deli; Qi, Wenjie (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionMycoplasma pneumoniae is one of the important pathogens of community-acquired pneumonia (CAP), and P1 adhesin serves as a pathogenic protein and an immune protein involved in the pathogenesis of mycoplasma pneumoniae. The aim of this study was to investigate the P1 adhesin genotype in Mycoplasma pneumoniae and its association with disease severity in patients with CAP from 2017 to 2019.MethodsM. pneumoniae was identified in patient samples by real-time quantitative polymerase chain reaction (qPCR). The P1 genotypes of samples were determined using a culture-independent P1 typing method.ResultsIn total, 1,907 clinical samples were collected from 13 tertiary hospitals in Beijing, Shenyang, and Baotou, including 1488 samples from children and 419 from adults. Of these, 820 samples (43.00%), including 777 from children and 43 from adults, were positive for M. pneumoniae. 797 samples were successfully typed using the culture-independent P1 typing method (P1-1, 605; P1- 2, 192). The M. pneumoniae detection rate and P1-1 detection rate differed significantly between children and adults (both p < 0.01), with P1-1 remaining the dominant genotype. The proportion of P1-2 samples increased in children from 16.75% in 2017 to 28.76% in 2019.DiscussionNo relationship between the P1 genotype and disease severity was identified. Monitoring the genotype changes of P1 adhesin in local populations may positively impact the epidemiological prevention and control of M. pneumoniae infections.